1997
DOI: 10.1557/jmr.1997.0142
|View full text |Cite
|
Sign up to set email alerts
|

Sol-gel Synthesis of LaAlO3; Epitaxial Growth of LaAlO3 Thin Films on SrTiO3(100)

Abstract: A LaAlO3 precursor solution was prepared via an all alkoxide sol-gel route. The solution of lanthanum methoxyethoxide and aluminum methoxyethoxide in 2-methoxyethanol was prepared via ligand exchange starting from lanthanum isopropoxide and aluminum sec-butoxide and was used to make both LaAlO3 powders and films. Complete hydrolysis of the solution formed a gel that yielded well-crystallized LaAlO3 powders when fired in air at 800 °C. A partially hydrolyzed solution was spun-cast on SrTiO3 (100) single crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…[6] However, there have been few reports of the successful deposition of LaAlO 3 films of high crystalline quality. The only reports in the literature to date have been of epitaxial LaAlO 3 films grown by pulsed laser deposition (PLD), [6,7] radio frequency (RF) magnetron sputtering, [8] and sol-gel [9] on perovskite substrates (SrTiO 3 and LaAlO 3 itself). Attempts to grow LaAlO 3 on Si, MgO, Al 2 O 3 , CeO 2 , and YSZ led to amorphous, or at best polycrystalline, films.…”
Section: Introductionmentioning
confidence: 99%
“…[6] However, there have been few reports of the successful deposition of LaAlO 3 films of high crystalline quality. The only reports in the literature to date have been of epitaxial LaAlO 3 films grown by pulsed laser deposition (PLD), [6,7] radio frequency (RF) magnetron sputtering, [8] and sol-gel [9] on perovskite substrates (SrTiO 3 and LaAlO 3 itself). Attempts to grow LaAlO 3 on Si, MgO, Al 2 O 3 , CeO 2 , and YSZ led to amorphous, or at best polycrystalline, films.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Moreover, the growing demand for fabrication of multilayer superconductor±insulator± superconductor (SIS) arrays, has spurred, over the past few years, intense scientific investigation on the growth of buffers, interlayers or overlayers suitable for high T c oxide films. Few studies have been reported on the growth of LaAlO 3 by physical vapor deposition (PVD) techniques [6] on Si substrates, and by sol±gel processes on sapphire [7] and SrTiO 3 [8] substrates. The metal±organic (MO) CVD technology proved an interesting alternative or complement to PVD techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Rolling assisted biaxially textured substrates are ideal templates for the solution process. A coated conductor is defined as the superconductor deposited on a long-length textured substrate.…”
Section: Introductionmentioning
confidence: 99%